The State of Alluvial Gold Exploration in Ghana. (Journal of Science and Technology, 2016)
The enactment in Ghana of Mining and Mineral Law 1986 or PNDCL 153 (Provisional National Defense Council Law 153) has led to an upsurge in the deploy-malt of large risk capital for the search and development of gold deposits. Of the three types of gold deposits found in Ghana (namely; primary Birimian lodes, paleoplacer Tarkvvaian Banket conglomerates and Recent placers) local investors appear more interested in working the Recent placer alluvial gold because of the lower capital required for the development of the younger unconsolidated alluvial gravels as against that of the older and compact Proterozoic deposits. However, the rather modest returns on investments in alluvial gold exploration arc beginning to frustrate many Ghanaian mining entrepreneurs.The lack of adequate local technical know-how in alluvial gold exploration, poor planning and haphazard execution of programmes coupled with inadequate flow of capital are often cited as the causes of the present lack of success. This article examines some of the reasons of these drawbacks and focuses on the methods used by two successful alluvial gold projects to serve as an archetype to both the exploration geologist and the investor. The study also advocates fortifying the law on mining to curtail the rise of mining-induced environmental degrading activities.